Efficient and safe lithium battery diaphragm and preparation method thereof
Through the structural design of polyimide and the use of CMC and SBR binders, lithium battery separators with high chemical stability and mechanical strength were prepared, which solved the high energy density and high power conditions of lithium battery separators in the prior art. The problem of insufficient safety has achieved high safety and comprehensive performance improvement of lithium batteries.
Patent Information
- Application Number
- CN202411458819.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing lithium battery separators cannot meet battery safety requirements under high energy density and high power conditions, and their performance cannot take into account high specific energy and high safety performance.
By designing and modifying the polyimide, combining CMC and SBR as binders, using inert atmosphere protection, casting method and vacuum oven heating, we can prepare high chemical stability, mechanical strength and high temperature resistance by using processes such as the inert atmosphere protection, casting method and vacuum oven heating. Characteristic lithium battery separator.
It significantly improves the safety and comprehensive performance of lithium batteries, including chemical stability, mechanical strength and thermal stability, can meet the safety requirements of high-capacity lithium-ion batteries, and exhibit good performance under high temperature conditions.
Smart Images

Figure BDA0005091266850000121 
Figure BDA0005091266850000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy technology, and in particular, relates to an efficient and safe lithium battery separator and a preparation method thereof. Background Art
[0002] In the structure of lithium batteries, the diaphragm is one of the key internal components. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. A diaphragm with excellent performance plays an important role in improving the overall performance of the battery. The main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. The diaphragm material is non-conductive, and its physical and chemical properties have a great influence on the performance of the battery.
[0003] Patent No. CN107221628A provides an efficient and safe lithium battery separator and a preparation method thereof, wherein PAN polymer is dissolved in a first portion of DMF solvent, nanocellulose is added to a second portion of DMF solvent, and stirred and dispersed evenly; PVP additive is added to the first portion of DMF solvent; the first portion of DMF solvent and the second portion of DMF solvent are mixed evenly; the casting solution is subjected to vacuum degassing treatment to remove bubbles in the mixed solution; the mixed solution without bubbles is placed in a film-making device to make a film. An efficient and safe lithium battery separator and a preparation method thereof of the present invention, the obtained lithium battery separator has excellent mechanical strength. A lithium battery separator is provided, which is obtained by any of the above-mentioned preparation methods, a lithium battery separator formed by three layers, the second layer has a plurality of finger-shaped holes, and the first layer and the third layer both have a plurality of air permeable holes. A lithium-ion battery is provided, comprising any of the above-mentioned lithium battery separators, and the battery cycle performance is better.
[0004] Patent No. CN106876641A discloses a lithium battery separator and its preparation method and application in lithium batteries. The lithium battery separator of the present invention is an inorganic nanofiber membrane. The inorganic component can enhance the thermal dimensional stability of the lithium battery separator, so that the lithium battery separator has high heat resistance and stability; the inorganic component can improve the wettability of the lithium battery separator with the electrolyte. The inorganic nanofiber membrane has a high porosity, which can improve the electrolyte absorption rate and ion conductivity of the lithium battery separator, which is beneficial to improve the cycle and rate performance of the lithium battery. The lithium battery separator prepared by the electrospinning technology adopted in the present invention has the advantages of high temperature resistance and high porosity. The obtained lithium battery separator can withstand high temperature treatment for a long time without obvious thermal shrinkage. The process for preparing the lithium battery separator of the present invention is simple and has high productivity. The prepared lithium battery separator can meet the safety requirements of high-capacity lithium-ion batteries.
[0005] At present, with the continuous increase in battery energy density, battery safety issues are becoming increasingly prominent. The performance of the diaphragms used in today's batteries can no longer meet the requirements of high-power, high-energy-density batteries. Therefore, it is an irreversible trend to develop battery diaphragms that have both high-energy-density and high-safety performance. Summary of the invention
[0006] In view of the problems described in the background technology, the inventors of the present invention propose an efficient and safe lithium battery separator and a preparation method thereof. The method prepares a polyimide separator for lithium batteries by structural design and modification of polyimide, and then uses CMC and SBR as binders for spraying, thereby improving the safety and comprehensive performance of the power battery.
[0007] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0008] An efficient and safe lithium battery separator and a preparation method thereof, characterized in that it comprises the following steps:
[0009] S1. Under the protection of an inert atmosphere, deionized water is added to a reaction tank, and then diamine monomers, aluminum oxide, and a novel diamine monomer with a quinone structure are added to the reaction tank, and stirred for 20 to 100 minutes to obtain a first mixed solution; then the first mixed solution is cooled to below 5°C, and a dianhydride monomer is added to obtain a second mixed solution, and the system temperature is kept below 5°C and stirred for 10 to 17 hours to obtain a polyamic acid solution, and then a solvent is added and stirred for 40 to 60 minutes to obtain a polyamic acid slurry;
[0010] S2, cooling the polyamic acid slurry obtained in step S1 to 5-15° C., then coating the polyamic acid slurry on an aluminum-plastic film by a doctor blade using a casting method to obtain a preformed polyamic acid film, sequentially passing through two coagulation baths and an extraction bath, and separating the aluminum-plastic film after the extraction is completed to obtain a polyamic acid film;
[0011] S3, drying the polyamic acid film obtained in step S2, and then heating it in a vacuum oven to obtain a polyimide separator for a lithium battery.
[0012] More preferably, the diamine monomer is selected from one or more of 1,4-bis(4-aminophenoxy)benzene, 2,2′-bistrifluoromethyl-4,4′-diaminodiphenyl ether, and 1,3,5-tris(4-aminophenoxy)benzene.
[0013] Further preferably, the dianhydride monomer is selected from one or more of pyromellitic anhydride, biphenyl tetracarboxylic anhydride, polyphenyl dianhydride, 1,2,4,5-pyromellitic anhydride, 3,6-bis(trifluoromethyl)-pyromellitic anhydride, 2,2-bis(3,4-dicarboxyphenyl)methane dianhydride, 3,5-bis(3,4-dicarboxyphenyl)biphenyl dianhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, binaphthalene dianhydride, cyclobutane dianhydride and 1,4-bis(phenylmaleic anhydride)benzene.
[0014] More preferably, the total mass of the diamine monomer and the dianhydride monomer accounts for 10 to 30 wt % of the mass of the polyamic acid solution.
[0015] More preferably, the mass ratio of the diamine monomer: the novel diamine monomer with a benzoquinone structure: aluminum oxide: dianhydride monomer is (1-1.4): (0.1-0.5): (0.05-0.5): (1-1.5).
[0016] More preferably, the preparation method of the novel diamine monomer having a benzoquinone structure is:
[0017] Add 7-14 parts of 2,5-diaminobenzoquinone, 6-12 parts of maleic acid diamine, 0.004-0.6 parts of epoxycyclohexyl-cage polysilsesquioxane and 150-200 parts of DMF into a stirring kettle and mix them, then add 2-5 parts of triethylamine, stir at 60-70°C for 1-3h, and then remove DMF by reduced pressure distillation to obtain a new diamine monomer with a benzoquinone structure.
[0018] More preferably, the mass fraction of deionized water in the polyamic acid slurry is 70-90wt% of the total solvent, the mass fraction of the solvent is 10-30wt% of the total solvent, and the solvent is selected from dimethyl carbonate (DMC) or ethyl methyl carbonate (EMC).
[0019] Further preferably, the drying is specifically as follows: the polyamic acid film is first dried at 55-65°C, then the adhesive is sprayed on the surface of the polyamic acid film with a precision high-pressure sprayer at a spraying speed of 2-5 mL / min, and after spraying, the film is dried for a second time at 100-105°C.
[0020] More preferably, the binder is selected from sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), and the binder is sprayed on the aluminum-plastic film, the base layer has a thickness of 10-12 microns, and the thickness of both sides is 1-2 microns.
[0021] Further preferably, the binder preparation method is as follows:
[0022] A1: dissolving sodium carboxymethyl cellulose (CMC) in deionized water to prepare an emulsion with a concentration of 1.0-2.5 wt%;
[0023] A2: Add conductive carbon black, and the concentration of carbon black is controlled at 0.8-1.6wt%;
[0024] A3: Add sodium carboxymethyl cellulose (CMC) and control the concentration of CMC to 4-5wt%;
[0025] A4: Finally, add styrene butadiene rubber (SBR), and the concentration of SBR is controlled at 4-5wt%.
[0026] Compared with the prior art, the present invention has the following technical effects:
[0027] 1) This method designs the structure of polyimide and introduces side chains into the main chain of the polyimide molecule to destroy the regularity and symmetry of the chain segments, effectively reducing the interaction between the molecular chains. The prepared polyimide membrane has the characteristics of high chemical stability, moderate porosity, high mechanical strength and low high-temperature thermal shrinkage, which is of great significance for improving the safety and electrochemical performance of power batteries.
[0028] 2) The present invention uses sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) and a conductive medium as a binder, which effectively improves its agglomeration and peeling properties, thereby facilitating further improvement of the comprehensive performance of the lithium battery.
[0029] 3) The epoxy cyclohexyl-cage polysilsesquioxane introduced as the cross-linking center can significantly improve the mechanical strength and thermal stability of the final product. Its unique nano-size effect and highly reactive epoxy groups can effectively increase the cross-linking density of the material.
[0030] 4) The units introduced through the amino-epoxy reaction not only enhance the functionality of the monomers, but also improve the surface properties of the materials, such as improving chemical resistance and electrochemical stability. For lithium battery separators, this can effectively improve their stability in the electrolyte and the overall performance of the battery. DETAILED DESCRIPTION
[0031] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the examples are all based on conventional experimental conditions. In addition, for those skilled in the art, without departing from the essence and scope of the present invention, various modifications or improvements to the material components and dosages in these embodiments are within the scope of the present invention.
[0032] Example 1
[0033] An efficient and safe lithium battery separator and a preparation method thereof, characterized in that it comprises the following steps:
[0034] S1. Under the protection of an inert atmosphere, deionized water is added to a reaction tank, and then diamine monomers, aluminum oxide, and a novel diamine monomer with a quinone structure are added to the reaction tank, and stirred for 20 minutes to obtain a first mixed solution; then the first mixed solution is cooled to below 5°C, and a dianhydride monomer is added to obtain a second mixed solution, and the system temperature is kept below 5°C and stirred for 10 hours to obtain a polyamic acid solution, and then a solvent is added and stirred for 40 minutes to obtain a polyamic acid slurry;
[0035] S2, cooling the polyamic acid slurry obtained in step S1 to 5° C., then coating the polyamic acid slurry on an aluminum-plastic film by a doctor blade using a casting method to obtain a preformed polyamic acid film, sequentially passing through two coagulation baths and an extraction bath, and separating the aluminum-plastic film after the extraction is completed to obtain a polyamic acid film;
[0036] S3, drying the polyamic acid film obtained in step S2, and then heating it in a vacuum oven to obtain a polyimide separator for a lithium battery.
[0037] The diamine monomer is selected from 1,4-bis(4-aminophenoxy)benzene.
[0038] The dianhydride monomer is selected from pyromellitic anhydride.
[0039] The total weight of the diamine monomer and the dianhydride monomer accounts for 10 wt % of the weight of the polyamic acid solution.
[0040] The mass ratio of the diamine monomer: the novel diamine monomer with benzoquinone structure: aluminum oxide: dianhydride monomer is 1:0.1:0.05:1.
[0041] The preparation method of the novel diamine monomer with benzoquinone structure is as follows:
[0042] 7 g of 2,5-diaminobenzoquinone (CAS: 1521-06-8), 6 g of maleic acid diamine, 0.004 g of epoxycyclohexyl-cage polysilsesquioxane and 150 g of DMF were added to a stirring kettle and mixed, and then 2 g of triethylamine was added. The mixture was stirred at 60° C. for 1 h, and then DMF was removed by reduced pressure distillation to obtain a new diamine monomer with a benzoquinone structure.
[0043] The mass fraction of deionized water in the polyamic acid slurry is 70wt% of the total solvent, the mass fraction of the solvent is 10wt% of the total solvent, and the solvent is selected from dimethyl carbonate (DMC).
[0044] The drying is specifically as follows: the polyamic acid film is first dried at 55°C, then the adhesive is sprayed on the surface of the polyamic acid film at a spraying speed of 2mL / min using a precision high-pressure sprayer, and then a second drying is performed at 100°C after the spraying is completed.
[0045] The adhesive is selected from sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The adhesive is sprayed on the aluminum-plastic film. The thickness of the base layer is 10 microns, and the thickness of both sides is 1 micron.
[0046] The binder preparation method is as follows:
[0047] A1: dissolving sodium carboxymethyl cellulose (CMC) in deionized water to prepare an emulsion with a concentration of 1.0 wt%;
[0048] A2: Add conductive carbon black, and the concentration of carbon black is controlled at 0.8wt%;
[0049] A3: sodium carboxymethyl cellulose (CMC) was added, and the concentration of CMC was controlled at 4wt%;
[0050] A4: Finally, styrene butadiene rubber (SBR) was added, and the concentration of SBR was controlled at 4wt%.
[0051] Example 2
[0052] An efficient and safe lithium battery separator and a preparation method thereof, characterized in that it comprises the following steps:
[0053] S1. Under the protection of an inert atmosphere, deionized water is added to a reaction tank, and then diamine monomers, aluminum oxide, and a novel diamine monomer with a benzoquinone structure are added to the reaction tank, and stirred for 50 minutes to obtain a first mixed solution; then the first mixed solution is cooled to below 5°C, and a dianhydride monomer is added to obtain a second mixed solution, and the system temperature is kept below 5°C and stirred for 12 hours to obtain a polyamic acid solution, and then a solvent is added and stirred for 45 minutes to obtain a polyamic acid slurry;
[0054] S2, cooling the polyamic acid slurry obtained in step S1 to 5° C., then coating the polyamic acid slurry on an aluminum-plastic film by a doctor blade using a casting method to obtain a preformed polyamic acid film, sequentially passing through two coagulation baths and an extraction bath, and separating the aluminum-plastic film after the extraction is completed to obtain a polyamic acid film;
[0055] S3, drying the polyamic acid film obtained in step S2, and then heating it in a vacuum oven to obtain a polyimide separator for a lithium battery.
[0056] The diamine monomer is selected from 2,2′-bis(trifluoromethyl)-4,4′-diaminodiphenyl ether.
[0057] The dianhydride monomer is selected from 3,6-bis(trifluoromethyl)-pyromellitic dianhydride.
[0058] The total weight of the diamine monomer and the dianhydride monomer accounts for 15 wt % of the weight of the polyamic acid solution.
[0059] The mass ratio of the diamine monomer: the novel diamine monomer with benzoquinone structure: aluminum oxide: dianhydride monomer is 1.1:0.2:0.2:1.2.
[0060] The preparation method of the novel diamine monomer with benzoquinone structure is as follows:
[0061] 9 g of 2,5-diaminobenzoquinone (CAS: 1521-06-8), 8 g of maleic acid diamine, 0.1 g of epoxycyclohexyl-cage polysilsesquioxane and 165 g of DMF were added to a stirring kettle and mixed, and then 3 g of triethylamine was added. The mixture was stirred at 65° C. for 2 h, and then DMF was removed by reduced pressure distillation to obtain a new diamine monomer with a benzoquinone structure.
[0062] The mass fraction of deionized water in the polyamic acid slurry is 80wt% of the total solvent, the mass fraction of the solvent is 15wt% of the total solvent, and the solvent is selected from ethyl methyl carbonate (EMC).
[0063] The drying process is as follows: the polyamic acid film is first dried at 55°C, then the adhesive is sprayed on the surface of the polyamic acid film at a spraying speed of 3 mL / min using a precision high-pressure sprayer, and then the film is dried for a second time at 100°C after the spraying is completed.
[0064] The adhesive is selected from sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The adhesive is sprayed on the aluminum-plastic film. The thickness of the base layer is 10 microns, and the thickness of both sides is 2 microns.
[0065] The binder preparation method is as follows:
[0066] A1: Dissolve sodium carboxymethyl cellulose (CMC) in deionized water to prepare a 1.5% emulsion;
[0067] A2: Add conductive carbon black, and the carbon black concentration is controlled at 1.2wt%;
[0068] A3: sodium carboxymethyl cellulose (CMC) was added, and the concentration of CMC was controlled at 4.2wt%;
[0069] A4: Finally, styrene butadiene rubber (SBR) was added, and the concentration of SBR was controlled at 4.2wt%.
[0070] Example 3
[0071] An efficient and safe lithium battery separator and a preparation method thereof, characterized in that it comprises the following steps:
[0072] S1. Under the protection of an inert atmosphere, deionized water is added to a reaction tank, and then diamine monomers, aluminum oxide, and a novel diamine monomer with a quinone structure are added to the reaction tank, and stirred for 75 minutes to obtain a first mixed solution; then the first mixed solution is cooled to below 5°C, a dianhydride monomer is added to obtain a second mixed solution, and the system temperature is kept below 5°C and stirred for 14 hours to obtain a polyamic acid solution, and then a solvent is added and stirred for 55 minutes to obtain a polyamic acid slurry;
[0073] S2, cooling the polyamic acid slurry obtained in step S1 to 12° C., then coating the polyamic acid slurry on an aluminum-plastic film by a doctor blade using a casting method to obtain a preformed polyamic acid film, and sequentially passing through two coagulation baths and an extraction bath, and after the extraction is completed, separating the aluminum-plastic film to obtain a polyamic acid film;
[0074] S3, drying the polyamic acid film obtained in step S2, and then heating it in a vacuum oven to obtain a polyimide separator for a lithium battery.
[0075] The diamine monomer is selected from 1,3,5-tris(4-aminophenoxy)benzene.
[0076] The dianhydride monomer is selected from 1,4-di(phenylmaleic anhydride)benzene.
[0077] The total weight of the diamine monomer and the dianhydride monomer accounts for 25 wt % of the weight of the polyamic acid solution.
[0078] The mass ratio of the diamine monomer: the novel diamine monomer with benzoquinone structure: aluminum oxide: dianhydride monomer is 1.25:0.4:0.2:1.4.
[0079] The preparation method of the novel diamine monomer with benzoquinone structure is as follows:
[0080] 12 g of 2,5-diaminobenzoquinone (CAS: 1521-06-8), 10 g of maleic acid diamine, 0.3 g of epoxycyclohexyl-cage polysilsesquioxane and 180 g of DMF were added to a stirring kettle and mixed, and then 4 g of triethylamine was added. The mixture was stirred at 65° C. for 2 h, and then DMF was removed by reduced pressure distillation to obtain a new diamine monomer with a benzoquinone structure.
[0081] The mass fraction of deionized water in the polyamic acid slurry is 85wt% of the total solvent, the mass fraction of the solvent is 25wt% of the total solvent, and the solvent is selected from dimethyl carbonate (DMC).
[0082] The drying is specifically as follows: the polyamic acid film is first dried at 65°C, then the adhesive is sprayed on the surface of the polyamic acid film with a precision high-pressure sprayer at a spraying speed of 4 mL / min, and after the spraying is completed, the film is dried for a second time at 105°C.
[0083] The adhesive is selected from sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The adhesive is sprayed on the aluminum-plastic film. The thickness of the base layer is 12 microns, and the thickness of both sides is 1 micron.
[0084] The binder preparation method is as follows:
[0085] A1: dissolving sodium carboxymethyl cellulose (CMC) in deionized water to prepare an emulsion with a concentration of 2.0 wt%;
[0086] A2: Add conductive carbon black, and the carbon black concentration is controlled at 1.4wt%;
[0087] A3: sodium carboxymethyl cellulose (CMC) was added, and the concentration of CMC was controlled at 4.8wt%;
[0088] A4: Finally, styrene butadiene rubber (SBR) was added, and the concentration of SBR was controlled at 4.8wt%.
[0089] Example 4
[0090] An efficient and safe lithium battery separator and a preparation method thereof, characterized in that it comprises the following steps:
[0091] S1. Under the protection of an inert atmosphere, deionized water is added to a reaction tank, and then diamine monomers, aluminum oxide, and a novel diamine monomer with a quinone structure are added to the reaction tank, and stirred for 100 minutes to obtain a first mixed solution; then the first mixed solution is cooled to below 5°C, and a dianhydride monomer is added to obtain a second mixed solution, and the system temperature is kept below 5°C and stirred for 17 hours to obtain a polyamic acid solution, and then a solvent is added and stirred for 60 minutes to obtain a polyamic acid slurry;
[0092] S2, cooling the polyamic acid slurry obtained in step S1 to 15° C., then coating the polyamic acid slurry on an aluminum-plastic film by a doctor blade using a casting method to obtain a preformed polyamic acid film, and sequentially passing through two coagulation baths and an extraction bath, and after the extraction is completed, separating the aluminum-plastic film to obtain a polyamic acid film;
[0093] S3, drying the polyamic acid film obtained in step S2, and then heating it in a vacuum oven to obtain a polyimide separator for a lithium battery.
[0094] The diamine monomer is selected from 2,2′-bis(trifluoromethyl)-4,4′-diaminodiphenyl ether.
[0095] The dianhydride monomer is selected from 1,4,5,8-naphthalenetetracarboxylic dianhydride.
[0096] The total weight of the diamine monomer and the dianhydride monomer accounts for 30 wt % of the weight of the polyamic acid solution.
[0097] The mass ratio of the diamine monomer: the novel diamine monomer with benzoquinone structure: aluminum oxide: dianhydride monomer is 1.4:0.5:0.4:1.2.
[0098] The preparation method of the novel diamine monomer with benzoquinone structure is as follows:
[0099] 14 g of 2,5-diaminobenzoquinone (CAS: 1521-06-8), 12 g of maleic acid diamine, 0.6 g of epoxycyclohexyl-cage polysilsesquioxane and 200 g of DMF were added to a stirring kettle and mixed, and then 5 g of triethylamine was added. The mixture was stirred at 70° C. for 3 h, and then DMF was removed by reduced pressure distillation to obtain a new diamine monomer with a benzoquinone structure.
[0100] The mass fraction of deionized water in the polyamic acid slurry is 90wt% of the total solvent, the mass fraction of the solvent is 30wt% of the total solvent, and the solvent is selected from ethyl methyl carbonate (EMC).
[0101] The drying is specifically as follows: the polyamic acid film is first dried at 65°C, then a binder is sprayed on the surface of the polyamic acid film at a spraying speed of 5 mL / min using a precision high-pressure sprayer, and then a second drying is performed at 105°C after the spraying is completed.
[0102] The adhesive is selected from sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The adhesive is sprayed on the aluminum-plastic film. The thickness of the base layer is 12 microns, and the thickness of both sides is 2 microns.
[0103] The binder preparation method is as follows:
[0104] A1: Dissolve sodium carboxymethyl cellulose (CMC) in deionized water to prepare an emulsion with a concentration of 2.5 wt%;
[0105] A2: Add conductive carbon black, and the carbon black concentration is controlled at 1.6wt%;
[0106] A3: Add sodium carboxymethyl cellulose (CMC) and control the CMC concentration at 5wt%;
[0107] A4: Finally, styrene butadiene rubber (SBR) was added, and the concentration of SBR was controlled at 5wt%.
[0108] Comparative Example 1
[0109] An efficient and safe lithium battery separator and a preparation method thereof, characterized in that it comprises the following steps:
[0110] S1. Under the protection of an inert atmosphere, deionized water is added to a reaction tank, and then a diamine monomer and aluminum oxide are added to the reaction tank, and stirred for 20 minutes to obtain a first mixed solution; then the first mixed solution is cooled to below 5°C, a dianhydride monomer is added to obtain a second mixed solution, and the system temperature is kept below 5°C and stirred for 10 hours to obtain a polyamic acid solution, and then a solvent is added and stirred for 40 minutes to obtain a polyamic acid slurry;
[0111] S2, cooling the polyamic acid slurry obtained in step S1 to 5° C., then coating the polyamic acid slurry on an aluminum-plastic film by a doctor blade using a casting method to obtain a preformed polyamic acid film, sequentially passing through two coagulation baths and an extraction bath, and separating the aluminum-plastic film after the extraction is completed to obtain a polyamic acid film;
[0112] S3, drying the polyamic acid film obtained in step S2, and then heating it in a vacuum oven to obtain a polyimide separator for a lithium battery.
[0113] The diamine monomer is selected from 1,4-bis(4-aminophenoxy)benzene.
[0114] The dianhydride monomer is selected from pyromellitic anhydride.
[0115] The total weight of the diamine monomer and the dianhydride monomer accounts for 10 wt % of the weight of the polyamic acid solution.
[0116] The mass ratio of the diamine monomer:aluminum oxide:dianhydride monomer is 1:0.05:1.
[0117] The mass fraction of deionized water in the polyamic acid slurry is 70wt% of the total solvent, the mass fraction of the solvent is 10wt% of the total solvent, and the solvent is selected from ethyl methyl carbonate (EMC).
[0118] The drying is specifically as follows: the polyamic acid film is first dried at 55°C, then the adhesive is sprayed on the surface of the polyamic acid film at a spraying speed of 2mL / min using a precision high-pressure sprayer, and then a second drying is performed at 100°C after the spraying is completed.
[0119] The adhesive is selected from sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The adhesive is sprayed on the aluminum-plastic film. The thickness of the base layer is 10 microns, and the thickness of both sides is 1 micron.
[0120] The binder preparation method is as follows:
[0121] A1: dissolving sodium carboxymethyl cellulose (CMC) in deionized water to prepare an emulsion with a concentration of 1.0 wt%;
[0122] A2: Add conductive carbon black, and the concentration of carbon black is controlled at 0.8wt%;
[0123] A3: sodium carboxymethyl cellulose (CMC) was added, and the concentration of CMC was controlled at 4wt%;
[0124] A4: Finally, styrene butadiene rubber (SBR) was added, and the concentration of SBR was controlled at 4wt%.
[0125] Comparative Example 2
[0126] The same as Example 1, except that the diaphragm is a commercially available PE diaphragm.
[0127] Evaluation of the embodiment:
[0128] 1. The separators prepared in the embodiments and comparative examples of the present invention were used to assemble batteries, and the safety performance of the batteries (refer to GB38031-2020) was tested. The test results are shown in Table 1. The procedure is as follows:
[0129] Lithium iron phosphate was used as the positive electrode active material, artificial graphite was used as the negative electrode active material, and the diaphragm prepared in the embodiment and the comparative example was used as the battery diaphragm. A 110Ah square aluminum shell battery was assembled and a charge and discharge test was carried out. The electrolyte was 1.0 mol / L LiPF6 / EC+DEC+EMC (1:1:1) electrolyte.
[0130] Table 1 Battery safety performance test results
[0131] project Over discharge Overcharge External short circuit 150℃ thermal shock extrusion acupuncture Example 1 OK OK OK OK OK OK Example 2 OK OK OK OK OK OK Example 3 OK OK OK OK OK OK Example 4 OK OK OK OK OK OK Comparative Example 1 OK OK OK OK OK NG Comparative Example 2 OK OK OK NG OK NG
[0132] 2. The separators prepared in the embodiments of the present invention and the comparative examples were used to assemble batteries, and the electrochemical performance of the batteries was tested. The test results are shown in Table 2. The test was performed as follows:
[0133] The positive electrode material was prepared with lithium iron phosphate and carbon black in a mass ratio of 4:1, the metal lithium sheet was used as the negative electrode material, the diaphragm prepared in the embodiment of the present invention and the comparative example was used as the diaphragm, the electrolyte was 1.0 mol / L LiPF6 / EC+DEC+EMC (1:1:1) electrolyte, the button cell was assembled, and after standing at room temperature for 24 hours, it was used for standby. The assembled battery was used to test the rate cycle charge and discharge performance at 1C, 2C, and 3C on the LANHE battery test system.
[0134] Table 2 Rate cycle charge and discharge performance test results
[0135]
[0136]
[0137] It can be seen from the above specific embodiments that the polyimide separator prepared by the method has a significant effect on improving the comprehensive performance of lithium-ion batteries, especially the safety performance, and has very important significance and broad application prospects.
[0138] The above description is an example of a specific implementation of the present invention, which is used to more clearly illustrate the inventive concept of the present invention, but it is not used to limit the scope of the claims of the present invention. According to the inventive concept of the present invention, those skilled in the art can easily modify and amend the above-mentioned embodiments, and these modifications and variations within the inventive concept of the present invention are all included in the scope of the claims attached to the present invention.
Claims
1. An efficient and safe lithium battery separator and a preparation method thereof, characterized in that: The following steps are involved: S1. Under the protection of an inert atmosphere, deionized water is added to a reaction tank, and then diamine monomers, aluminum oxide, and a novel diamine monomer with a quinone structure are added to the reaction tank, and stirred for 20 to 100 minutes to obtain a first mixed solution; then the first mixed solution is cooled to below 5°C, and a dianhydride monomer is added to obtain a second mixed solution, and the system temperature is kept below 5°C and stirred for 10 to 17 hours to obtain a polyamic acid solution, and then a solvent is added and stirred for 40 to 60 minutes to obtain a polyamic acid slurry; S2, cooling the polyamic acid slurry obtained in step S1 to 5-15° C., then coating the polyamic acid slurry on an aluminum-plastic film by a doctor blade using a casting method to obtain a preformed polyamic acid film, sequentially passing through two coagulation baths and an extraction bath, and separating the aluminum-plastic film after the extraction is completed to obtain a polyamic acid film; S3, drying the polyamic acid film obtained in step S2, and then heating it in a vacuum oven to obtain a polyimide separator for a lithium battery.
2. The highly efficient and safe lithium battery separator and preparation method thereof according to claim 1, characterized in that: The diamine monomer is selected from one or more of 1,4-bis(4-aminophenoxy)benzene, 2,2′-bistrifluoromethyl-4,4′-diaminodiphenyl ether, and 1,3,5-tris(4-aminophenoxy)benzene.
3. The highly efficient and safe lithium battery separator and preparation method thereof according to claim 1, characterized in that: The dianhydride monomer is selected from one or more of pyromellitic anhydride, biphenyl tetracarboxylic anhydride, polyphenyl dianhydride, 1,2,4,5-pyromellitic anhydride, 3,6-bis(trifluoromethyl)-pyromellitic anhydride, 2,2-bis(3,4-dicarboxyphenyl)methane dianhydride, 3,5-bis(3,4-dicarboxyphenyl)biphenyl dianhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, binaphthalene dianhydride, cyclobutane dianhydride and 1,4-bis(phenylmaleic anhydride)benzene.
4. The highly efficient and safe lithium battery separator and preparation method thereof according to claim 1, characterized in that: The total mass of the diamine monomer and the dianhydride monomer accounts for 10-30wt% of the mass of the polyamic acid solution, and the mass ratio of the diamine monomer: the new diamine monomer with a benzoquinone structure: aluminum oxide: dianhydride monomer is (1-1.4): (0.1-0.5): (0.05-0.5): (1-1.5).
5. The efficient and safe lithium battery separator and preparation method thereof according to claim 1, characterized in that: The preparation method of the novel diamine monomer with benzoquinone structure is as follows: Add 7-14 parts of 2,5-diaminobenzoquinone, 6-12 parts of maleic acid diamine, 0.004-0.6 parts of epoxycyclohexyl-cage polysilsesquioxane and 150-200 parts of DMF into a stirring kettle and mix them, then add 2-5 parts of triethylamine, stir at 60-70°C for 1-3h, and then remove DMF by reduced pressure distillation to obtain a new diamine monomer with a benzoquinone structure.
6. The efficient and safe lithium battery separator and preparation method thereof according to claim 1, characterized in that: The mass fraction of deionized water in the polyamic acid slurry is 70-90wt% of the total solvent, the mass fraction of the solvent is 10-30wt% of the total solvent, and the solvent is selected from dimethyl carbonate (DMC) or ethyl methyl carbonate (EMC).
7. A highly efficient and safe lithium battery separator and a method for preparing the same according to claim 1, characterized in that: The drying is specifically as follows: the polyamic acid film is first dried at 55-65°C, then a binder is sprayed on the surface of the polyamic acid film at a spraying speed of 2-5 mL / min using a precision high-pressure sprayer, and after spraying, a second drying is performed at 100-105°C.
8. The efficient and safe lithium battery separator and preparation method thereof according to claim 7, characterized in that: The adhesive is selected from sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The adhesive is sprayed on the aluminum-plastic film. The thickness of the base layer is 10-12 microns, and the thickness of both sides is 1-2 microns.
9. The efficient and safe lithium battery separator and the preparation method thereof according to claim 8, characterized in that: The binder preparation method is as follows: A1: dissolving sodium carboxymethyl cellulose (CMC) in deionized water to prepare an emulsion with a concentration of 1.0-2.5 wt%; A2: Add conductive carbon black, and the concentration of carbon black is controlled at 0.8-1.6wt%; A3: Add sodium carboxymethyl cellulose (CMC) and control the concentration of CMC to 4-5wt%; A4: Finally, add styrene butadiene rubber (SBR), and the concentration of SBR is controlled at 4-5wt%.
10. A lithium battery separator prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of high-elasticity and high-heat-resistance polyimide
CN111154100A
Preparation method of modified polyimide lithium ion battery diaphragm
CN111430642A
Polyimide diaphragm for lithium battery and preparation method of polyimide diaphragm
CN115636976A
Polyimide lithium ion battery diaphragm and preparation method thereof
CN117810644A
Lithium battery diaphragm as well as preparation method and application thereof
CN118231956A
